2018
DOI: 10.3233/npm-1799
|View full text |Cite
|
Sign up to set email alerts
|

Tube dependency as a result of prematurity

Abstract: Prematurity, especially extreme prematurity, is associated with an increased risk for development of tube dependency. Preventive measures for this specific group of children should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In a prospective study conducted in Austria as part of the initiative to wean tube feeds, out of the 711 children enrolled in the cohort, 53% were preterm, and a majority (two thirds) of the preterm infants were on tube feeds since birth. The authors also reported that amongst the extreme preterm infants, 83.5% had no other diagnosis except prematurity and its complications, pointing towards a strong association between feeding tube dependency and prematurity [ 34 , 35 ].…”
Section: Feeding Problems In Preterm Infants Beyond the Nicumentioning
confidence: 99%
“…In a prospective study conducted in Austria as part of the initiative to wean tube feeds, out of the 711 children enrolled in the cohort, 53% were preterm, and a majority (two thirds) of the preterm infants were on tube feeds since birth. The authors also reported that amongst the extreme preterm infants, 83.5% had no other diagnosis except prematurity and its complications, pointing towards a strong association between feeding tube dependency and prematurity [ 34 , 35 ].…”
Section: Feeding Problems In Preterm Infants Beyond the Nicumentioning
confidence: 99%
“… Help in generating quick sucking reflex-Due to incapability to produce effective sucking, preterm & very low birth weight infants often require enteral nutritional support (tube feeding) 49 since birth.…”
Section: Dental Interventionmentioning
confidence: 99%
“…Infants born preterm are at high risk to develop oral dysfunction [44,45]. The occurrence of comorbidities, such as bronchopulmonary dysplasia (BPD) or neurodevelopmental impairment can hinder the physiological development of oral skills, and some authors reported that more than 15% of preterm infants were discharged on enteral feeding (tube feeding) [46].…”
Section: Complementary Feeding Strategies For Infants With Oral Dysfumentioning
confidence: 99%